2014
DOI: 10.2134/agronj13.0387
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Yield‐Based Drought Tolerance Indices for Screening Safflower Genotypes

Abstract: Drought tolerance is not often considered an independent trait by plant breeders because the collective result of many traits of a plant with positive or negative interactions may be fairly general and polygenic in nature. The objective of this study was to evaluate six drought tolerance indices, namely the stress susceptibility index (SSI), yield stability index (YSI), tolerance index (TOL), mean productivity (MP), geometric mean productivity (GMP), and stress tolerance index (STI), to be used in screening sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 10 publications
4
45
0
Order By: Relevance
“…The TOL and SSI indices were positively correlated with grain yield under irrigated condition, while they were negatively correlated with grain yield under rainfed condition. The observed relations were in agreement with those reported by Bahrami et al (2014) in safflower and Nouri et al (2011) in durum wheat. Fernandez (1993) that selection based on STI, GMP and MP would identify genotypes with higher levels of yield potential and stress tolerance, whereas, SSI and TOL indices had a significant negative correlation with seed yield under stress conditions but a positive correlation with seed yield under non-stress conditions.…”
Section: Relationships Between Drought Tolerance Indices and Traitssupporting
confidence: 93%
“…The TOL and SSI indices were positively correlated with grain yield under irrigated condition, while they were negatively correlated with grain yield under rainfed condition. The observed relations were in agreement with those reported by Bahrami et al (2014) in safflower and Nouri et al (2011) in durum wheat. Fernandez (1993) that selection based on STI, GMP and MP would identify genotypes with higher levels of yield potential and stress tolerance, whereas, SSI and TOL indices had a significant negative correlation with seed yield under stress conditions but a positive correlation with seed yield under non-stress conditions.…”
Section: Relationships Between Drought Tolerance Indices and Traitssupporting
confidence: 93%
“…This cluster was also superior to grand mean of all other traits averaged over all clusters, indicating that this cluster contained desirable genotypes according to yield obtained from both environments and selection indices. This study is in line with previous reports that stated genotypes can be classified adapted to moisture-stressed and non-stressed conditions using cluster analysis in various crops (Eivazi et al, 2013;Johari-Pireivatlou, 2014;Bahrami et al, 2014;Sory et al, 2017). Generally, this study showed that selection can be improved though MRP, MP, GMP, STI, and HM.…”
Section: Cluster Analysissupporting
confidence: 92%
“…Thus plants may modify architecture by reducing the branch numbers as observed in our experiment, thus implying an alteration in the balance between source and sinks, to overcome salinity stress. It appears that root as the sink organ plays a crucial role in conferring salinity tolerance in safflower as is the case for drought tolerance (Bahrami et al, 2014). Deeper root growth is not only a mechanism to avoid moisture deficits but also important for adaptation to salinity because roots would use water of higher potential in the subsoil where less salts accumulated.…”
Section: Resultsmentioning
confidence: 99%